ASSISTANCE FOR YOUTH GENERATION BASED ON THE PREPARATION OF SIMPLE FINANCIAL STATEMENTS ON MSMEs IN DRANGONG TAMAN KOTA SERANG - Syamsudin, Syamsudin; Entis Haryadi; Yoga Adiyanto (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this dedication for the Young Generation is to provide assistance and counseling to individuals or small entrepreneurs, especially micro and small MSMEs in Drangong Taman Kota Serang about practical and simple knowledge about managing simple finances in accordance with the principles of financial management. The research method used is the classical method with a discussion approach, question and answer, and simulation with the intention that the material can be well received by partners. It is hoped that after this service program is carried out, the participants will have the knowledge and insight as small entrepreneurs who are skilled in managing finances and are also able to look for opportunities to increase family finances as a provision to improve their standard of living for the better.